2008
DOI: 10.1016/s0210-4806(08)73917-2
|View full text |Cite
|
Sign up to set email alerts
|

Cistectomía radical como tratamiento del cáncer vesical infiltrante en el paciente de edad avanzada

Abstract: Radical cystectomy could be performed in carefully selected elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…15 Similarly, age and cardiac disease are also independent risk factor for postoperative complication. 16 In a prospective study, patients of ASA 3 or more were found susceptible to complications. 17 There were altogether 5 (15.6%) mortality in our study when all the 32 cases were taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, age and cardiac disease are also independent risk factor for postoperative complication. 16 In a prospective study, patients of ASA 3 or more were found susceptible to complications. 17 There were altogether 5 (15.6%) mortality in our study when all the 32 cases were taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Hollenbeck et al [26] also identified several independent risk factors for postoperative morbidity: age, a history of dyspnea, chronic steroid use and an ASA ≥3. Similarly, March et al [27] identified age and cardiac disease as independent risk factors for major complications. Zebic et al [16] reported ASA 4 as a significant risk factor for mortality while complications and mortality were not different between ASA 2 and ASA 3 in their series.…”
Section: Discussionmentioning
confidence: 99%